Arthritis of mice induced by Mycoplasma pulmonis: humoral antibody and lymphocyte responses of CBA mice. - Cole, B C (1975)
Peak arthritis occurred 14 days after intravenous injection of Mycoplasma pulmonis and persisted in some mice at low levels for 84 days. A marked lymphocytosis occurred during the first week of infection with only a slight increase in polymorphonuclear leukocytes. Complement-fixing antibodies appeared in low titer 3 days after infection and moderate levels persisted for 84 days. The metabolic-inhibiting and mycoplasmacidal antibody responses were absent or minimal. M. pulmonis appeared to be mitogenic for mouse lymphocytes as evidenced by (i) increased uptake of [3H]thymidine for normal lymphocytes exposed to various concentrations of nonviable M. pulmonis antigen, and (ii) a 13-fold increase in [3H]thymidine uptake in lymphocytes taken from mice 3 days after infection with M. pulmonis in the absence of added antigen. Lymphocytes taken from infected mice transformed significantly more at all time periods than control lymphocytes when exposed to M. pulmonis antigen. This response was maximal at 3 days and minimal at 21 to 35 days after infection. Lymphocytes sensitized to M. pulmonis did not transform when exposed to M. arthritidis antigen or vice versa. M. pulmonis infection had no effect upon the mitogenic responses of lymphocytes to phytohemagglutinin or lipopolysaccharide. There was no statistically significant correlation between persistence of arthritis and degree of humor antibody or lymphocyte responses. However, persisting arthritis was associated with a higher incidence of mycoplasma isolations.